Maqashid Syariah as a Foundation Social Based Crowdfunding (Comparison of Indonesian and Malaysian Sharia Economic Law) - Kusmiadi, Kusmiadi; Maruf, Irma Rachmawati; Ruslina, Elli; Noor, Zakhiri Md (IHSA Institute, 2025)
Maqashid Sharia, which is the purpose and basic principle of Sharia, serves as a moral and ethical foundation in the development of various economic activities. The method used is a qualitative approach to explore the relevance of Maqashid Syariah in Social Based Crowdfunding contracts. This method was chosen to obtain an in-depth understanding of the concept of Maqashid Syariah and its application in the context of Islamic economic law in Indonesia and Malaysia. Based on the analysis conducted, it can be concluded that Maqashid Syariah has significant relevance as a foundation in Social Based Crowdfunding contracts in Indonesia and Malaysia. Maqashid Syariah, which focuses on achieving the goals and benefits of society, can ensure that every Crowdfunding transaction is not only financially beneficial, but also in accordance with sharia principles. Social Based Crowdfunding based on Maqashid Syariah is able to answer the needs of the community by providing access to financing for beneficial projects, such as social, education, and health. This approach also promotes justice and equality in resource distribution, reduces inequality, and supports small entrepreneurs who need support. Agreements structured based on Maqashid Syariah principles emphasise the importance of transparency and accountability, so that all parties involved can be held accountable for their roles and contributions